2019
DOI: 10.1007/s10143-019-01097-1
|View full text |Cite
|
Sign up to set email alerts
|

Periodontitis and gingival bleeding associate with intracranial aneurysms and risk of aneurysmal subarachnoid hemorrhage

Abstract: Oral bacteria DNA has been found in intracranial aneurysms (IA) and a high prevalence of periodontitis was reported in IA patients. We investigated whether periodontitis associates with IA formation and aneurysmal subarachnoid hemorrhage (aSAH). First, we compared in a case-control setting the prevalence of periodontal disease in IA patients (42 unruptured IA, 34 ruptured IA) and in age-and gender-matched controls (n = 70) from the same geographical area (Health 2000 Survey, BRIF8901). Next, we investigated wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
48
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 35 publications
(54 citation statements)
references
References 34 publications
4
48
0
1
Order By: Relevance
“…Recently, our group found the association with periodontitis, formation of intracranial aneurysms (IA), and the risk of aneurysmal subarachnoid hemorrhage (aSAH) [25]. Together with the prior reports that DNA of oral bacteria is found in the wall of many ruptured intracranial aneurysms [64,65], these results raised the intriguing question whether periodontitis and oral bacteria participate to the formation of IAs and to their progression towards rupture.…”
Section: Introductionmentioning
confidence: 78%
See 4 more Smart Citations
“…Recently, our group found the association with periodontitis, formation of intracranial aneurysms (IA), and the risk of aneurysmal subarachnoid hemorrhage (aSAH) [25]. Together with the prior reports that DNA of oral bacteria is found in the wall of many ruptured intracranial aneurysms [64,65], these results raised the intriguing question whether periodontitis and oral bacteria participate to the formation of IAs and to their progression towards rupture.…”
Section: Introductionmentioning
confidence: 78%
“…Periodontitis has also been associated with atherosclerosis, stroke [38,46,63], and abdominal aortic aneurysms (AAA) [12,45,79]. Very recently, our group showed that periodontitis or gingivitis associate also with aSAH and IA formation [25]. In addition to this, another recent study reported an association between aSAH and being a carriage of specific strains of Streptococcus mutans, a significant contributor to tooth decay [31].…”
Section: Intracranial Aneurysms Show Chronic Inflammation That Is Assmentioning
confidence: 89%
See 3 more Smart Citations